1976
DOI: 10.1029/wr012i003p00392
|View full text |Cite
|
Sign up to set email alerts
|

The age of groundwater in the chalk of the London Basin

Abstract: Isotope techniques have been applied to a study of groundwater movement in the Chalk of the London Basin. The 'age' of the water as determined by •4C measurements increases toward the central confined part of the basin where it exceeds 25,000 years and therefore originated during the Pleistocene. The age distribution supports previous interpretations of the permeability pattern, partly based on hydrochemistry. Measurements of tritium and the Stable isotope ratios of carbon, oxygen, and deuterium were also made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 5 publications
(2 reference statements)
3
30
0
Order By: Relevance
“…Foster and Smith-Carington (1980) identified by-pass flow through macropores (both microfissures and large pores) in chalk from a balance calculation of tritium in the unsaturated zone and suggested that up to 15% of the tritium was transported by the preferential flow of water through macropores. The fraction of water moving in this way in chalk in England has been estimated as 6-15% of total water movement (Smith et al 1976). This type of flow is currently thought to occur principally during heavy rainstorms.…”
Section: Discussionmentioning
confidence: 99%
“…Foster and Smith-Carington (1980) identified by-pass flow through macropores (both microfissures and large pores) in chalk from a balance calculation of tritium in the unsaturated zone and suggested that up to 15% of the tritium was transported by the preferential flow of water through macropores. The fraction of water moving in this way in chalk in England has been estimated as 6-15% of total water movement (Smith et al 1976). This type of flow is currently thought to occur principally during heavy rainstorms.…”
Section: Discussionmentioning
confidence: 99%
“…fingerprinting sources of water leakage (Butler and Verhagen, 1997;Maréchal and Etcheverry, 2003), to the regional, e.g. groundwater resource and quality studies (Smith et al, 1976;Rauert et al, 1993), the archaeological (Iacumin et al, 1997;White et al, 1998), the environmental (Andrews et al, 1997;Iacumin and Longinelli, 2002), the quasi-forensic (Keenlyside et al, 1997) and ultimately as part of the global mosaic which aids the understanding of climatic processes (Rozanski et al, 1993;Hoffmann et al, 2000). In contrast to some areas of Europe, such as Germany and Italy (Förstel and Hützen, 1983;Longinelli and Selmo, 2003), the stable isotopic variations of waters in the British Isles have hitherto not been summarised in any systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…The other end member is the d 13 C value of soil CO 2 . Smith et al (1976) quoted an average UK value of K26.1G 0.3 ‰. Other factors affecting the d 13 C TDIC values of the groundwater are the degree of openness of the system and the extent of bacterial respiration in the aquifer.…”
Section: C Tdic and 14 C Agesmentioning
confidence: 97%